Parental Resources and College Attendance: Evidence from Lottery Wins - George Bulman; Robert W. Fairlie; Sarena Goodman; Adam Isen (Institute of Labor Economics (IZA), 2020)
We examine U.S. children whose parents won the lottery to trace out the effect of financial resources on college attendance. The analysis leverages federal tax and financial aid records and substantial variation in win size and timing. While per-dollar effects are modest, the relationship is weakly concave, with a high upper bound for amounts greatly exceeding college costs. Effects are smaller among low-SES households, not sensitive to how early in adolescence the shock occurs, and not moderated by financial aid crowd-out. The results imply that households derive consumption value from college and household financial constraints alone do not inhibit attendance.
Keywords: I20; I22; I24; 330; college; attendance; parental resources; financial constraints; lottery winnings; administrative data